2012
DOI: 10.1590/s1517-83822012000100044
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm production by clinical Staphylococci strains from canine otitis

Abstract: This study determined the species of 54 staphylococci isolates from canine otitis and their ability to produce biofilm through the Congo red agar method, confirmed by scanning electron microscopy. The most frequently identified species were S. intermedius and S. simulans. Results showed that 30% of the strains were biofilm producers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…In this study, all S. pseudintermedius clinical OE isolates produced biofilm, but 80% of these isolates (MSSP = 12, MRSP = 4) were weak biofilm producers regardless of their resistance profile. In contrast, a previous study found that only 39.3% of S. pseudintermedius (previously identified as S. intermedius ) isolated from canine OE were biofilm producers, but no further classification of biofilm formation was undertaken (Moreira et al, ). Another study revealed that 98% ( n = 140) of S. pseudintermedius isolated from dogs with skin, wound and surgical infections were biofilm producers with the majority (61%) being strong biofilm producers (Singh, Walker, Rousseau, & Weese, ).…”
Section: Discussionmentioning
confidence: 93%
“…In this study, all S. pseudintermedius clinical OE isolates produced biofilm, but 80% of these isolates (MSSP = 12, MRSP = 4) were weak biofilm producers regardless of their resistance profile. In contrast, a previous study found that only 39.3% of S. pseudintermedius (previously identified as S. intermedius ) isolated from canine OE were biofilm producers, but no further classification of biofilm formation was undertaken (Moreira et al, ). Another study revealed that 98% ( n = 140) of S. pseudintermedius isolated from dogs with skin, wound and surgical infections were biofilm producers with the majority (61%) being strong biofilm producers (Singh, Walker, Rousseau, & Weese, ).…”
Section: Discussionmentioning
confidence: 93%
“…This suggested a higher pathogenicity for the strain, increasing resistance of bacteria and consequent recurrence of chronic otitis cases (OLIVEIRA et al, 2005). In another article, the author considers biofilm forming isolates presenting as black colonies in CRA, and reported the ability of S. intermedius isolates to form biofilms (11%) (MOREIRA et al, 2012). In the present study, we considered these colonies as only SL producers; although, in such colonies a high rate of biofilm formation has already been reported (MOREIRA et al, 2012).…”
Section: Discussionmentioning
confidence: 72%
“…The ability of each strain to produce biofilm was quantified spectrophotometrically as previously described (8,9). Biofilm production was induced in a flat-bottomed well of a 96-well microtiter plate, using brain heart infusion broth (Oxoid, Basingstoke, Hampshire, England) enriched with 1% glucose.…”
mentioning
confidence: 99%
“…Biofilm production was induced in a flat-bottomed well of a 96-well microtiter plate, using brain heart infusion broth (Oxoid, Basingstoke, Hampshire, England) enriched with 1% glucose. The plates were incubated for 48 h at 37°C (8,9), and each well was dyed with 0.25% crystal violet, after washing with phosphate-buffered saline (PBS). Based on the obtained optical density values at 570 nm (OD 570 ), the strains were classified as nonproducers, weak producers, moderate producers, or strong producers, as described by Stepanovic et al (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation